From Attachment to a Sacred Figure to Loyalty to a Sacred Route: The Walking Pilgrimage of Arbaeen - Adel Nikjoo; Mohammad Sharifi-Tehrani; Mehdi Karoubi; Abolfazl Siyamiyan (Religions, 2020)
Around 20 million Shia pilgrims shape one of the world’s biggest pilgrimages in Iraq, called “Arbaeen,” many of whom walk long distances to Karbala city as a part of the ritual every year. Faith in Imam Hussein, who was martyred in the battle of Karbala in 680 CE, is central among all pilgrims in this ritual, but the main question is how do the pilgrims’ faith and psychological cognitions translate into this spiritual journey with different meanings during the Arbaeen pilgrimage? The present study aims to discover the different social and psychological reasons for pilgrims’ feelings of attachment to Imam Hussein and to the Arbaeen pilgrimage route. Through 57 semi-structured in-depth interviews with pilgrims in two phases, Arbaeen 2014 and 2019, four different perceived roles for Imam Hussein including beloved, interceding, transformative, and unifier figure were found, leading pilgrims to feel an attachment to him. The current study mainly contributes to the literature by presenting an empirical analysis of Muslims’ experiences and perceptions of Islamic theology, and their loyalty to a sacred route through attachment to a sacred figure.